Invasive Mole Resulting in Uterine Rupture: A Case Report - Wu, Anshan; Zhu, Qiong; Tan, Chang; Chen, Long; Tao, Yin (Frontiers in Surgery, 2022)
Uterine surgery is a common predisposing factor for uterine rupture, while an invasive mole that leads to uterine rupture is a rare clinical occurrence. Here, we report a case of a 31-year-old childless woman who underwent abortion after 53 days of pregnancy. She still experienced abdominal pain and scanty vaginal bleeding after the abortion. Her levels of human chorionic gonadotropin (HCG) were high, while ultrasound and MRI results revealed an enlarged uterus and a mass in the myometrium. During preparation for treatment, the gynecologist ruptured the uterus of the patient, leaving her shocked. Eventually the patient's uterus was removed the uterus and pathologically diagnosed as result is the an invasive mole.